Trauma, Stress, and Resilience Among Sexual Minority Women : Rising Like the Phoenix. - Balsam, Kimberly (Taylor and Francis, 2012)
Prevent victimization of sexual minority women by raising your awareness level! Trauma, Stress, and Resilience Among Sexual Minority Women: Rising Like the Phoenix is the first resource to examine trauma, violence, and stress as experienced by lesbian and bisexual women. You'll gain a better understanding of the stressors that these women experience, including the cultural/social trauma of living with homophobia and heterosexism as well as the individual traumas of verbal, physical, and sexual abuse. This book contains never-before-seen data that investigates the prevalence, impact, a.